DEVELOPING STUDENTS’ WORKBOOK OF READING SKIL BASED ON INQUIRY BASED LEARNING FOR THE TENTH GRADE STUDENTS SMA SWASTA BUDISATRYA MEDAN - Rivia Nabilah Larasati Pasaribu; Indra Hartoyo; Farida Hanim Saragih (Universitas Negeri Medan, 2019)
ABSTRACT This study aims to: (1) find out the reading skill workbook used in tenth grade in SMA Swasta Budisatrya Medan, (2) determine the workbook needed by tenth grade students in reading skills, and (3) to develop valid workbooks for use in reading skills according to the needs of tenth grade students. The research was conducted by using the Research and Development method from Borg and Gall, Gall (2003). The research subject was X IPA 1 students of SMA Swasta Budisatrya. The research object is an inquiry based learning workbook. The instrument used was student questionnaire. The data was collected using questionnaires validation sheets. The validator consists of material expert, english teacher practitioner and the one class of tenth grade students. The data were analyzed using descriptive analysis. The results of the study show that: (1) the workbook that used does not support inquiry based learning processes, (2) inquiry-based learning based workbooks are workbooks needed by students, and (3) the developed inquiry based learning workbooks have been valid with a percentage of 91.2% from expert material and 92.8% from the English teacher and this workbook is appropriate with students' needs for reading skills.Keywords: Inquiry Based Learning, Reading, Students’ Workbook